A real options approach to tender offers and acquisitions processes - José Pablo Dapena; Santiago Fidalgo (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2003)
Corporate control has added value for an investor since it gives degrees of freedom about the use of assets, sources of finance, salaries, etc. On the other hand, real options create value through the flexibility associated to the ability to react to some relevant uncertainty. The process of acquisition of corporate control can have two real options associated, a waiting option and a growth option. In the waiting option value is created through sequential investment instead of investing at once, while the growth option carries all the private benefits the investor can seize from control by making follow up investments, which can also justify premiums paid above the former market price. A relevant proposition of our paper is that the exercise price of the growth option (and hence the amount to be paid as the control premium) can be affected by the release of information. We develop a model for these two theoretical extremes, one where the exercise price fully reacts to events, and one where the exercise price does not react at all, and we obtain that the timing of the process of acquiring control would depend on the reaction of the price to be paid to obtain control, so would the size of the control premium over the former price.
Keywords: G13; G31; G34; 330; Übernahme; Theorie; Realoptionsansatz